2020
DOI: 10.1021/acsami.0c09393
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Rare Earth Elements onto DNA-Functionalized Mesoporous Carbon

Abstract: The recovery and separation of rare earth elements (REEs) are of national importance owing to the specific usages, high demand, and low supply of these elements. In this research, we have investigated the adsorption of rare earth elements onto DNA-functionalized mesoporous carbons with a BET surface area of 605 m 2 /g and a median mesopore width of 48 Å. Three types of single-stranded DNA, one with 100 base units of thymine, another with 20 units of thymine, and the third, a 2000 unit long DNA from salmon milt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…In our previous work, we have also demonstrated that different REEs, including Nd and Dy, can be adsorbed on phosphorus-functionalized activated carbon and DNA-grafted mesoporous carbon. Our X-ray absorption near-edge structure (XANES) analysis confirmed that the oxidation state is not altered in the DNA-grafted carbon and EXAFS confirmed the binding of Nd with O and P functionalities …”
Section: Introductionsupporting
confidence: 55%
See 4 more Smart Citations
“…In our previous work, we have also demonstrated that different REEs, including Nd and Dy, can be adsorbed on phosphorus-functionalized activated carbon and DNA-grafted mesoporous carbon. Our X-ray absorption near-edge structure (XANES) analysis confirmed that the oxidation state is not altered in the DNA-grafted carbon and EXAFS confirmed the binding of Nd with O and P functionalities …”
Section: Introductionsupporting
confidence: 55%
“…In addition, it is also observed that an adsorbed amount followed the trend of Lu < Dy < La. It essentially suggests that the adsorbed amount increases with the increase in the atomic radius (Lu = 173 pm; Dy = 178 pm; La = 187 pm) . This effect has been further elaborated in Figure c.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations